Thin Films: Enhanced Raman Scattering of CuPc Films on Imperfect WSe2 Monolayer Correlated to Exciton and Charge‐Transfer Resonances (Adv. Funct. Mater. 52/2018). (27th December 2018) - Liu, Yanran; Gao, Zhibin; Chen, Ming; Tan, Yang; Chen, Feng
Abstract : In article number1805710, Yang Tan, Feng Chen, and co‐workers demonstrate that the surface‐enhanced Raman scattering performance of a WSe2 monolayer can be enhanced via tailoring the atomic ratio of WSe2 ; this correlates to the exciton and charge‐transfer resonances. For an atomic ratio of 1.96, the maximum enhancement factor on irradiated WSe2 is more than 120, which is enhanced by more than 40 times compared with pristine WSe2 .